Association of coagulation markers and antiphospholipid antibodies with ischemic and bleeding risk in patients with atrial fibrillation undergoing percutaneous coronary intervention. (3rd October 2022) - Anfang, V; Gjermeni, D; Szabo, S; Vetter, H; Hesselbarth, D; Leggewie, S; Bode, C; Duerschmied, D; Trenk, D; Olivier, C B
Abstract: Background: Antiphospholipid antibodies and other coagulation markers are associated with ischemic risk in patients with coronary artery disease without oral anticoagulation (OAC). Aim: To assess the association of antiphospholipid antibodies (aPL) and conventional markers of coagulation with ischemic and bleeding risk in patients with atrial fibrillation (AF) undergoing percutaneous coronary intervention (PCI). Patients and methods: In this prospective single center observational cohort study, patients with AF and an indication for OAC were enrolled after PCI. Dilute Russell's viper venom time (DRVVT) was used to determine lupus anticoagulants (LA) in direct OAC-free plasma. Anti-cardiolipin IgG (aCL), IgM and anti-beta2GP-1-IgG (aβ2GP1) were analyzed by enzyme linked immunosorbent assay (ELISA). Fibrinogen C (FIBC), d-dimers and prothrombin fragments 1 and 2 (PF1+2) were measured in citrated plasma. Immature platelet fraction (IPF [%]) and absolute (IPF abs. [103/μl]) were measured in EDTA-blood. The primary ischemic outcome was defined as time to major adverse cardiovascular events (MACE: all-cause death, myocardial infarction, or stroke) assessed at 6 months. Bleeding was defined according to the International Society of Thrombosis and Haemostasis (ISTH) and the Bleeding Academic Research Consortium (BARC). Results: 158 patients were enrolled between May 2020 and May 2021. The median age was 78 years (interquartile range, IQR 72–82), 111 (70%) were male, and 39 (25%) presented with acute coronary syndrome. All Patients were treated with clopidogrel and OAC, 145 (92%) in addition with acetylsalicylic acid (ASA). 32 patients (20%) had ≥1 antiphospholipid antibody (aPL; LA: 19 [12%], aCL: 14 [9%], aβ2GP1: 2 [1%]). D-dimers were elevated in 74 patients (47%), FIBC was increased in 40 (25%) and PF1+2 in 68 patients (43%). IPF [%] was elevated in 28 (18%) and IPF abs. [103/μl] in 11 (7%). The presence of aPL was neither significantly associated with MACE, nor with bleeding risk. Elevated d-dimers were significantly associated with higher risk for MACE (HR=5.1, 95% CI [1.1; 23.4], p=0.04), major ISTH bleeding events (HR= 6.9, 95% CI [1.5; 30.8], p=0.01) and BARC bleeding type 3 or 5 (HR=6.4, 95% CI [1.4; 28.7], p=0.02). Increased levels of FIBC were associated with risk of MACE (HR= 3.6, 95% CI [1.1; 12.0], p=0.03 (Table 1). Conclusion: In patients with AF undergoing PCI, high levels of d-dimers and fibrinogen C indicate an increased ischemic risk. Elevated d-dimers are associated with higher risk for bleeding. aPL positivity was not significantly associated with outcome possibly due to low sample size. A combined panel of biomarkers might be suitable to assess ischemic and bleeding risk in patients with AF following PCI. Funding Acknowledgement: Type of funding sources: Public Institution(s). Main funding source(s): Faculty of Medicine, Freiburg